Injuries in adolescent female players in European football: a prospective study over one outdoor soccer season - Soderman, K.; Adolphson, J.; Lorentzon, R.; Alfredson, H. (Scandinavian Journal of Medicine & Science in Sports, 2001)
In this prospective study, injuries in 153 adolescent female soccer players were recorded during one outdoor season (April-October). The overall injury incidence rate was 6.8 per 1000 h soccer (games and practice) and the incidence rate of traumatic injury 9.1 and 1.5 per 1000 player-hours in games and practice, respectively. Sixty-three players (41%) sustained 79 injuries. Sixty-six percent of the injuries were traumatic and 34% were overuse injuries. Most of the traumatic injuries occurred during games. Eighty-nine percent of the injuries were located in the lower extremities and 42% occurred in the knee or ankle. The most frequent type of injury was ankle sprain (22.8%). Forty-one percent of the traumatic injuries and 56% of the ankle sprains were re-injuries. Most of the injuries were of moderate severity (52%), while 34% were minor and 14% were major. Most of the major injuries were traumatic such as knee ligament injuries and ankle sprains.